Intravenous transplantation of mouse embryonic stem cells attenuates demyelination in an ICR outbred mouse model of demyelinating diseases - Kidsadagon Pringproa (2018)
© 2016, Editorial Board of Neural Regeneration Research. All rights reserved. Induction of demyelination in the central nervous system (CNS) of experimental mice using cuprizone is widely used as an animal model for studying the pathogenesis and treatment of demyelination. However, different mouse strains used result in different pathological outcomes. Moreover, because current medicinal treatments are not always effective in multiple sclerosis patients, so the study of exogenous cell transplantation in an animal model is of great importance. The aims of the present study were to establish an alternative ICR outbred mouse model for studying demyelination and to evaluate the effects of intravenous cell transplantation in the present developed mouse model. Two sets of experiments were conducted. Firstly, ICR outbred and BALB/c inbred mice were fed with 0.2% cuprizone for 6 consecutive weeks; then demyelinating scores determined by luxol fast blue stain or immunolabeling with CNPase were evaluated. Secondly, attenuation of demyelination in ICR mice by intravenous injection of mES cells was studied. Scores for demyelination in the brains of ICR mice receiving cell injection (mES cells-injected group) and vehicle (sham-inoculated group) were assessed and compared. The results showed that cuprizone significantly induced demyelination in the cerebral cortex and corpus callosum of both ICR and BALB/c mice. Additionally, intravenous transplantation of mES cells potentially attenuated demyelination in ICR mice compared with sham-inoculated groups. The present study is among the earliest reports to describe the cuprizone-induced demyelination in ICR outbred mice. Although it remains unclear whether mES cells or trophic effects from mES cells are the cause of enhanced remyelination, the results of the present study may shed some light on exogenous cell therapy in central nervous system demyelinating diseases.